Brief Report: HIV-1 Evolution in Breakthrough Infections in a Human Trial of Oral Pre-exposure Prophylaxis With Emtricitabine and Tenofovir Disoproxil Fumarate - Ruone, Susan (J Acquir Immune Defic Syndr, 2016)
We describe HIV-1 evolutionary dynamics in the 4 participants from the TDF2-PrEP trial who became HIV-1 infected while prescribed emtricitabine and tenofovir disoproxil fumarate (FTC/TDF). At seroconversion, virus diversity in the 2 participants with detectable drug was only 0.05% (95% confidence intervals: 0.04 to 0.06) and 0.07% (0.06 to 0.08) compared with 2.25% (1.95 to 2.6) and 0.42% (0.36 to 0.49) in those with no detectable drug and 0.07%–0.69% in 5 placebo recipients (P > 0.5). At 10 months, diversity in adherent participants was only 0.37% (0.31 to 0.41) and 0.86% (0.82 to 0.90) compared with 0.5%–1.7% among participants who did not take FTC/TDF (P > 0.5). Although limited by the small number of infections that reduced the power to detect differences, we found that sequences from seroconverters with detectable drug were more homogeneous than those from placebo or nonadherent seroconverters.